PERAN PERCEIVED VALUE DAN FREQUENCY CONSUMPTION TERHADAP REPURCHASE INTENTION KONSUMSI BUAH DI MASA PANDEMI COVID-19 - Audrina, Sheila Okthalia; Immanuel, Dewi Mustikasari (Parsimonia - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of healthy consumption, perceived price fairness, and perceived quality on repurchase intention to consume fruits during the COVID-19 pandemic with frequency consumption as a moderator and perceived value as a mediator. Questionnaire data is processed using PLS. The population in this study were people who had bought fruit in Surabaya and Sidoarjo. The sampling technique used was purposive sampling with a total sample of 386 respondents. The results of this study indicate that healthy consumption, perceived price fairness, and perceived quality have a positive effect on repurchase intention, and perceived value provides a full mediating effect, while frequency consumption as a moderator is found to weaken the effect of healthy consumption on repurchase intention. Keywords: Healthy consumption, frequency consumption, perceived price fairness, perceived quality, perceived value, and repurchase intention.